Construction of a hybrid lung model by combining a real geometry of the upper airways and an idealized geometry of the lower airways. (November 2020) - Agujetas, R.; Barrio-Perotti, R.; Ferrera, C.; Pandal-Blanco, A.; Walters, D.K.; Fernández-Tena, A.
Highlights: A hybrid model of the human lung airway has been constructed using images obtained from computed tomography (CT) and an idealized morphology. An intermediate solid model section links the cylindrical sections of the idealized model to the non-cylindrical sections of the CT-based model. The model was verified using two sets of simulations, steady inspiration/ expiration and transient simulation of forced spirometry. The model development outlined here represents an important step toward computational simulation of lung dynamics for patient-specific applications. Abstract: Background and Objective: Health care costs represent a substantial an increasing percentage of global expenditures. One key component is treatment of respiratory diseases, which account for one in twelve deaths in Europe. Computational simulations of lung airflow have potential to provide considerable cost reduction and improved outcomes. Such simulations require accurate in silico modeling of the lung airway. The geometry of the lung is extremely complex and for this reason very simple morphologies have primarily been used to date. The objective of this work is to develop an effective methodology for the creation of hybrid pulmonary geometries combining patient-specific models obtained from CT images and idealized pulmonary models, for the purpose of carrying out experimental and numerical studies on aerosol/particle transport and deposition in inhaled drug delivery. Methods: For the construction of the hybrid numerical model, lung images obtained from computed tomography were exported to the DICOM format to be treated with a commercial software to build the patient-specific part of the model. At the distal terminus of each airway of this portion of the model, an idealization of a single airway path is connected, extending to the sixteenth generation. Because these two parts have different endings, it is necessary to create an intermediate solid to link them together. Physically realistic treatment of truncated airway boundaries in the model was accomplished by mapping of the flow velocity distribution from corresponding conducting airway segments. Results: The model was verified using two sets of simulations, steady inspiration/expiration and transient simulation of forced spirometry. The results showed that the hybrid model is capable of providing a realistic description of air flow dynamics in the lung while substantially reducing computational costs relative to models of the full airway tree. Conclusions: The model development outlined here represents an important step toward computational simulation of lung dynamics for patient-specific applications. Further research work may consist of investigating specific diseases, such as chronic bronchitis and pulmonary emphysema, as well as the study of the deposition of pollutants or drugs in the airways.